PENGABDIAN MASYARAKAT INTERNASIONAL: PENYULUHAN PENTINGNYA PENDIDIKAN BAGI ANAK-ANAK BURUH MIGRAN DI SANGGAR BIMBINGAN SENTUL, KUALA LUMPUR, MALAYSIA - Shadu Satwika Wijaya; Slamet Rosyadi; Muhammad Yamin; Agus Ganjar Runtiko; Ahmad Sabiq; Muslih Faozanudin; Erwin Sunarya; Zaula Rizqi Atika (Department of Public Administration, University Wijaykusuma Purwokerto, 2024)
Children of migrant workers often face barriers in accessing quality education, which can negatively impact their development and future. This international community service aims to raise the awareness of migrant workers' parents about the importance of education for their children through counseling conducted at Sentul Commmunity Learning Service, Kuala Lumpur, Malaysia. The activity involved 20 parents of Guidance Studio students. The counseling used a participatory and inclusive approach, taking into account the participants' cultural and linguistic backgrounds. The results of this activity showed positive changes in parents' perceptions and attitudes towards education, with increased awareness of the role of education in breaking the cycle of poverty and social marginalization. Nonetheless, achieving sustainable change requires a collaborative and holistic effort involving various stakeholders, including the government, schools, civil society organizations and academics. This community service contributes to the literature on the education of migrant workers' children and emphasizes the importance of involving parents as active partners in expanding access to education for this marginalized group.